The goldilocks days represent optimal time-use to prevent obesity, low physical performance, risk and fear of falling in older adults - Vindiš, Jan; Pelclová, Jana; Jašková, Paulína; Hron, Karel (Scientific reports, 2025)
This study introduces the concept of the "Goldilocks Day" - the optimal 24-hour time-use of intensity- or posture-specific composition specifically tailored for young-old (65-70 years) and old-old (> 70 years) adults. We aimed (1) to describe optimal 24-hour time-use of compositions for each health outcome, and (2) identify the 'Goldilock Day' for all outcomes together. This approach, involving backwards pivot coordinates (bpcs), we provide a clearer interpretation of physical behavior data, offering practical insights for healthy aging. Data were collected from 309 older adults (65 + years) in Czechia, using accelerometers worn on the non-dominant wrist to assess intensity-specific behaviors (sedentary behavior - SB, light physical activity - LPA, moderate-to-vigorous physical activity - MVPA, and sleep) and on the right thigh and waist to assess posture-specific behaviors (lying, sitting, standing, moving, and walking). Health outcomes included body mass index (BMI), fall risk, fear of falling, and overall physical performance as assessed by the Short Physical Performance Battery. Compositional regression models, based on the bpcs, were used to assess the relationships between time-use and these outcomes. In young-old adults, the time-use composition for optimal BMI included 7.5 h of sleep, 12.0 h of SB, 3.2 h of LPA, and 1.4 h of MVPA. Old-old adults displayed slightly lower MVPA (1.0 h) and increased SB (12.8 h). Generally, higher MVPA and lower SB were associated with better physical performance and reduced fear of falling. The optimal "Goldilocks Day" for both age groups highlighted the benefits of higher physical activity and reduced sedentary time, with significant implications for personalized health recommendations and improved health outcomes in Czech older adults.
Keywords: Sedentary Behavior; Male; Obesity; strach; Česká republika; obezita; akcelerometrie; Aged; Fear; mužské pohlaví; senioři; Physical Functional Performance; Exercise; úrazy pádem; postura těla; Czech Republic; Accidental Falls; Compositional data analysis; senioři nad 80 let; lidé; sedavý životní styl; ženské pohlaví; Humans; Body Mass Index; Aged, 80 and over; Posture-specific behavior; Posture; index tělesné hmotnosti; Accelerometry; tělesná a funkční výkonnost; Physical behavior; Female; cvičení